AUTOMATIC MARKING BOT FOR SOLAR PANEL INSTALLATION. - SAKTHI, P.; KIRUTHIKA, S.; ABISHEK, K. S.; DHANUSH, B.; SAKTHIVEL, J.; KUMAR, V. YESVANTH (Turkish Journal of Physiotherapy Rehabilitation, 2021)
Solar power is a form of energy undertaken from the force and rays of the sun. This energy is inexhaustible, and a green form of energy. The most important accepted technique for extracting energy from the sun's rays is through sun powered boards. The solar panel installation in rooftops is a tedious process which involves a huge labour work. The process of marking the solar panel position in the roof is often carried out only in early morning and during the night time, as the reflection of sunlight on roof makes the sheet surface's heat so high. So the time consumed for marking the position alone is high which makes the installation process slower. In this proposed idea the automatic bot has been developed for marking the installation position of solar panel in the rooftop which reduces the man power intervention and also accelerating the installationprocess.